Identification and characterization of Csa-miR159s and their expression patterns under different abiotic stresses in cucumber (Cucumis sativus L.) - Zhao, Zhenxiang; Ao, Wenhong; Luo, Weirong; Sun, Yaoguang; Tokala, Vijay Yadav; Liu, Junjun; Zhi, Shenshen; Sun, Yongdong (Frontiers in Plant Science, 2025)
The miR159 gene family plays an essential role in plant growth and development, and stress response. Nevertheless, there are no reports defining its specific function in cucumber fruit expansion and response to abiotic stresses. In this study, we retrieved six Csa-miR159 sequences from the EnsemblPlants database, which were located on chromosome 1, chromosome 3, and chromosome 5 of cucumber, respectively. Phylogenetic analysis showed that Csa-miR159c/d/e/f belonged to one branch and Csa-miR159a/b to another. Cis-acting regulatory elements (CREs) including light response elements, phytohormone response elements, stress response elements, regulatory elements associated with plant growth and development were distributed unevenly in the promoter regions of Csa-miR159s, which indicated that Csa-miR159s might mediate the stress response, and growth and development. Moreover, it was determined that CsMYBs were the target genes of Csa-miR159s through psRNA-Target prediction and qRT-PCR analysis. Further findings suggested that Csa-miR159b might negatively regulate cucumber fruit expansion by targeting Cs1RMYB9, Cs1RMYB31, Cs2RMYB37 and Cs2RMYB64. Similarly, Csa-miR159d might negatively regulate cucumber fruit expansion by targeting Cs2RMYB27 and Cs2RMYB32. In addition, the differential expression of Csa-miR159s suggested their potential response to abiotic stresses and plant phytohormones. This study would provide valuable information on the molecular characterization of Csa-miR159s and establish a foundation for further research on the mechanisms of Csa-miR159s in regulating fruit expansion and stress response.